(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2022)
Trauma is the 6th leading cause of death worldwide resulting in 5 million of all deaths. It is the 5th leading cause of significant disability. In Egypt, injuries the fifth leading cause of death and the most common cause of hospitalization and account for at least 1/4 of all inpatients. The aim is to identify the medico-legal importance of different causes of orthopedic trauma to patient admitted at Beni-Suef university hospital and identify their relation with different demographic data of the patient. Data of 207 patients with orthopedic trauma admitted at Beni-Suef university hospital period from September 2016 to December 2016. Age, sex, residence, cause, site, number of trauma, type of fracture, investigation done, treatment and also associated other injuries are reported. The most common cause of trauma is motorcycle accidents (25.6%) followed by fall on ground (25.1%). Lower extremities are the most common site of trauma (44.9%). Most of cases have single fracture (71.5%) with simple type (50.3%). X-ray is the most common investigation done to patients (71%). (68.1%) of cases need operative treatment. (84%) of cases came with orthopedic trauma only not associated with other injury. While the most common associated injury is wounds over skin (5.4%). Limb injuries are a common problem among the physically active, and such injuries may result in diminished performance, reduced participation, and in the longer term loss of function, chronic joint disease, and disability. Limb injuries represent the commonest form of injury involved in road traffic accidents